Effect of different irrigation and tillage methods on yield and resource use efficiency of boro rice (Oryza sativa) - Karim, MR; Alam, MM; Ladha, JK; Islam, MS; Islam, MR (Bangladesh Academy of Sciences, 2014)
An experiment was carried out in Bangladesh Agricultural Research Institute (BARI) farm during 2010-11 to evaluate yield and resource use efficiency of transplanted boro rice under two tillage and three irrigation methods. Two tillage methods viz., conventional tillage with puddle transplanted rice and reduced tillage unpuddled transplanted rice and three irrigation methods viz., sprinkler irrigation, alternate wetting and drying (AWD) and flood irrigation were used as treatment variables. Grain yield was 7.62% higher in sprinkler and 4.72% higher in AWD irrigation method over flood irrigation method. Irrespective of tillage methods, reduced tillage method holds 4.62% higher yield production over conventional tillage method. Water use efficiency was found highest in sprinkler irrigation method (0.83 kg/m3) and in reduced tillage method (0.773 kg/m3). Labour required for land preparation was 15 md/ha in reduced tillage, whereas it was 38 md/ha in conventional tillage method. Seedling uprooting and transplanting required higher labour in reduced tillage method over conventional tillage. Fuel consumptions (49.78 l/ha) and electricity (3475.11 Kwhr/ha) was also less in reduced tillage method. Reduced tillage had less land preparation and fuel cost over conventional tillage method. But seedling uprooting and transplanting cost was higher in reduced tillage. Irrigation and total cost of production was 7753 Tk./ha and 69972 Tk./ha in Sprinkler × RT method. Benefit cost ratio was also higher in sprinkler irrigation (1.81) and reduced tillage method (1.82). DOI: http://dx.doi.org/10.3329/bjar.v39i1.20165 Bangladesh J. Agril. Res. 39(1): 151-163, March 2014